Transforming a General Hospital to an Infectious Disease Hospital for COVID-19 Over 2 Weeks - Pandey, Navin; Kaushal, Vipin; Puri, Goverdhan Dutt; Taneja, Sunil; Biswal, Manisha; Mahajan, Pranay; Guru, Rashmi Ranjan; Malhotra, Pankaj; Sehgal, Inderpaul Singh; Dhooria, Sahajal; Muthu, Valliappan; Agarwal, Ritesh (Frontiers in Public Health, 2020)
Pandemics like the coronavirus disease (COVID)-19 can cause a significant strain on the healthcare system. Healthcare organizations must be ready with their contingency plans for managing many patients with contagious infectious disease. Ideally, every large hospital should have a facility that can function as a high-level isolation unit. An isolation unit ensures that the healthcare staff and the hospital are equipped to deal with infectious disease outbreaks. Unfortunately, such facilities do not exist in several hospitals, especially in resource-limited settings. In such a scenario, healthcare setups need to convert their existing general structure into an infectious disease facility. Herein, we describe our experience in transforming a general hospital into a functional infectious disease isolation unit.